2013
DOI: 10.1007/s00256-013-1704-6
|View full text |Cite
|
Sign up to set email alerts
|

Relationship between stress ankle radiographs and injured ligaments on MRI

Abstract: ATFL injury and PTFL injury on MRI significantly affected tibiotalar tilt angle and anterior drawer on stress radiographs. Other factors, such as age and gender, need to be considered in evaluating radiographic lateral ankle instability.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
27
1
3

Year Published

2015
2015
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 36 publications
(32 citation statements)
references
References 34 publications
1
27
1
3
Order By: Relevance
“…One cause of variability in ankle stress radiographs may be unidentified determinants. A previous study reported that females showed a 1.5 ° larger tibiotalar tilt angle than males, and the angle decreased 0.05 ° per 1-year increase in age [25]. However, this study did not consider the influence of the bony configuration of the ankle.…”
Section: Degree Of Ligament Injury Was Evaluated On Anklementioning
confidence: 79%
See 4 more Smart Citations
“…One cause of variability in ankle stress radiographs may be unidentified determinants. A previous study reported that females showed a 1.5 ° larger tibiotalar tilt angle than males, and the angle decreased 0.05 ° per 1-year increase in age [25]. However, this study did not consider the influence of the bony configuration of the ankle.…”
Section: Degree Of Ligament Injury Was Evaluated On Anklementioning
confidence: 79%
“…On ankle MRI, ATFL was assessed on axial images, and CFL, posterior talofibular ligaments (PTFL), and deltoid ligaments were evaluated on coronal images. Ligament injuries were classified as intact, partial injury, or complete injury [25]. The presence of ankle joint effusion was also recorded.…”
Section: Consensus Building and Measurementsmentioning
confidence: 99%
See 3 more Smart Citations